Process improvement on the lipase-catalyzed synthesis of oleyl palmitate, a wax ester via response surface methodology (RSM) - Salina Mat Radzi; Siti Salhah Othman; Hanina Mohd Noor; Yunus , Nor Mona,; Basri, Mahiran,; Abdul Rahman, Mohd Basyaruddin,; Muhammad, Syamsul Kamar (David Publishing, USA, 2024)
Non-Indexed Publication